Bisalbuminaemia, a family trait: case report (Portuguese Journal of Family Medicine and General Practice, 2025)
Introduction: Human serum albumin is the most abundant serum protein in plasma and plays several essential roles. Among the various polymorphisms in its expression is bisalbuminaemia. This phenotype can be hereditary, a relatively rare genetic condition, or transient (secondary). Case description: We present a 4-year-old male child with food selectivity and no abnormalities on physical examination. An analytical assessment revealed iron deficiency anaemia and a protein electrophoresis pattern of bisalbuminaemia, with no other abnormalities. The innate form was presumed to be a genetic cause, and the mother was asked to undergo protein electrophoresis, which showed an identical pattern, corroborating this hypothesis. Iron supplementation was started, and a reassessment confirmed the ferropenic anaemia correction and the bisalbuminaemia pattern’s maintenance. Comment: Hereditary bisalbuminaemia has a low prevalence in the population, however recognising this pattern is particularly important in clinical practice, especially in the context of primary healthcare. Early identification of this benign variant allows the family doctor to guide the patient appropriately, clarifying the genetic and non-pathological nature of the condition and avoiding unnecessary interventions.
Keywords: Blood protein electrophoresis; Serum albumin; Bisalbuminaemia; Case report